Sócrates épico, trágico e cômico: um estudo sobre os gêneros literários no Eutidemo, Banquete e Apologia - Ribeiro, José André (2017)
The proposal of this work is to provide an analysis of Socrates as a character of Plato’s dialogues. What is meant to show is that this character joins elements of the epic, tragic and comic genres. We assume that Socrates is represented as a kind of philosophical hero, in which epic features merge with a comic mask, whose nuances also bring a tragic dramatization. In view of this, this study identifies the relation of the dialogues with the poetic tradition, from the analysis of some dialogues, which would allow to draw that sense of the character. First, the "Euthydemus" as a comic piece. Second, the epic character of Socrates in the speech of Alcibiades from the Simposium. Finally, an analysis of the encounter between the genres on the character of Apology.